An Analysis of Frequent Job-hopping and Turnover Intention on University Graduates in China--The Empirical Study of 120 College Graduates in Beijing Sport University - Zhang, Xiaolin (2014)
As graduates of higher education to train senior personnel, because of its high quality and strong plasticity loved by enterprises, most enterprises are in favour of recruiting new college graduates employees. However, because of the enrollment expansion policy of higher education in China, the amount of college graduates has been growing considerably, there has relatively talent surplus in college students' employment market which resulted in the high rate of college graduates turnover especially in the newly recruited staff of two to three years, one side is severe employment pressure, one side is frequent turnover, this situation to the enterprise as well as college graduates are adversely affected to varying degrees, stable job market for college students but also caused a certain degree of impact. Therefore, the study of the influence factors on college graduates intention to leave frequently have some practical significance. The main statistical methods used in the research involve item analysis,factor analysis, analysis of variance, correlation analysis and regression analysis. Some ineffective questions were deleted from the questionnaire through item analysis. In factor analysis some questions were rationally adjusted, and the reliability and validity of the questionnaire were verified; by the analysis of variance,the individual factors of college graduates' intention to quit were found out:through the relevant and regression analysis,the influential factors of college graduates turnover intention were concluded,and the Predicted model was revised according to the results of the analysis.Finally,the paper advanced some suggestions for the enterprises against the high graduates' turnover rate on the basis of the concluded factors in the research.